Pengembangan Kapasitas Masyarakat Pelaku Usaha di Daerah Penyangga Taman Nasional Laut Bunaken Provinsi Sulawesi Utara - Londa, Very Y. (Sam Ratulangi University, 2020)
People take advantage of the potential and position of Bunaken Marine National Park to support their survival through business activities. This research was conducted to find a model for developing the community capacity of business actors in the buffer zone of Bunaken Marine National Park. This study used a qualitative design, data obtained through interviews, observation, and secondary data collection. The findings of this study are that the building of community capacity of business actors in the buffer areas of Bunaken Marine National Park, North Sulawesi Province is more carried out in program implementation through training activities to strengthen knowledge and skills. Strengthening capacity has not been able to provide the right motivation and assistance for business actors. The concept that can be put forward as the findings of this study is that the development of community capacity in business actors is related to aspects of human resources and institutions. Development of human resource capacity through the dimensions of training for knowledge and skills as well as assistance to motivate and control business development. Capacity building in business institutions is related to strengthening business capital, business facilities and business management.